f(1)=999
now
f(1)+f(2)+...+f(n)=n^2*f(n)
f(1)+f(2)+...+f(n-1)=(n-1)^2*f(n-1)
so we have
(n-1)^2*f(n-1)+f(n)=n^2*f(n)
(n-1)^2*f(n-1)=(n^2-1)*f(n)
(n-1)^2*f(n-1)=(n+1)(n-1)*f(n)
(n-1)*f(n-1)=(n+1)*f(n)
f(n)=(n-1)*f(n-1)/(n+1)
so
f(1)=999
f(2)=f(1)/3
f(3)=2*f(2)/4=2*f(1)/12=f(1)/6
f(4)=3*f(3)/5=(3*2)*f(1)/(3*4*5)=f(1)/10
so in seems that it follows the patern
f(n)=2*f(1)/(n^2+n)
now to prove this using induction
f(1)=2*f(1)/(1+1)=2*f(1)/2=f(1)
thus it holds for initial value
assume it holds for f(n-1)
from definition derived above
f(n)=(n-1)*f(n-1)/(n+1)
substitute f(n-1)=2*f(1)/[n*(n-1)]
f(n)=(n-1)*[2*f(1)/[n*(n-1)]]/(n+1)
(n-1)'s drop out and we are left with
f(n)=2*f(1)/(n*(n+1))
thus if it holds for n-1 it holds for n
thus it holds for all n>=1
|
Posted by Daniel
on 2008-10-31 14:36:05 |